Oleohepathography - Davidenko, Nicolás; Silva García, Ernesto; Rivero, Isaac; Vallone, Amanda (Cirugía del Uruguay, 1973)
1) The procedure was applied on 28 patientes, 16 of which were females and 12 males ranging between 25 and 71 years of age. In 17 cases splenic percutaneous approach was employed, in 10 repermeated umbilical approach and in one case the approach was ileal intraoperatory. 2) After determining portal pressure, hydrosoluble contrast was used in detecting possible azygo-portal or porto-cava communications or bivenous shunts (portasuprahepatic), for in this case the method is contraindicated Twenty ce. of were injected and became apparent three phases: portal, sinusoid and hepatic. The latter had been described by the. author in 1969 from the radiological angle. 3) Radiocinematography, performed in 6 patients, brought out new facts of portal hemodynamics, indicating the possibility of measuring circulatory speed. 4) We analyzed the results obtained during the different intra and juxtahepatic expansive processes and the procedure proved to be efficient and inocuous. Two nodules ½ cm. in diameter were observed. It also proved to be efficient in post-operatory control of the adventitions hydatid cavity, as well as in studyirtg local circulatory condition in compensatory hepatic atrophies or hypertrophies. 5) Hystological study 10 patients indicated that the hepatic phase described in radiological observation was present. The lipidic excess in the hepatic cell and in Kupfer's cells was observed, as well as its subsequent dispersa! and fragmentation; no other citoarchitectural alterations were observed.